THE NEXT-GENERATION SEQUENCYG BY RBCL GENE OF FRESHWATER ORGANISM FOR MONITORING OF SREDNY KABAN LAKE - Sverdrup, Anthony; Frolova, Ludmila; Lazareva, Anna (Revista Inclusiones, 2019)
The paper presents the results of analysis and an assessment of water quality of the Sredny Kaban Lake (Kazan, Russia) based on the rbcL gene of freshwater organisms by the method of sequencing a new generation. A comparative analysis of metagenomic data shows that most of the organisms of Lake Sredny Kaban are grouped by the RBCL gene near the b-mesosaprobity. Lake Sredny Kaban can be characterized as polluted, according to the quality of water, transitional to b-mesosaprobic.